The high-performance technology CRISPR/Cas9 improves knowledge and management of acute myeloid leukemia - Romeo Gabriel Mihaila (Palacký University Olomouc, Faculty of Medicine and Dentistry, 2021)
Knowledge on acute myeloid leukemia pathogenesis and treatment has progressed recently, but not enough to provide ideal management. Improving the prognosis of acute myeloid leukemia patients depends on advances in molecular biology for the detection of new therapeutic targets and the production of effective drugs. The CRISPR/Cas9 technology allows gene insertions and deletions and it is the first step in investigating the function of their encoded proteins. Thus, new experimental models have been developed and progress has been made in understanding protein metabolism, antitumor activity, leukemic cell maintenance, differentiation, growth, apoptosis, and self-renewal, the combined pathogenetic mechanisms involved in leukemogenesis. The CRISPR/Cas9 system is used to understand drug resistance and find solutions to overcome it. The therapeutic progress achieved using the CRISPR/Cas9 system is remarkable. FST gene removal inhibited acute myeloid leukemia cell growth. Lysine acetyltransferase gene deletion contributed to decreased proliferation rate, increased apoptosis, and favored differentiation of acute myelid leukemia cells carrying MLL-X gene fusions. The removal of CD38 gene from NK cells decreased NK fratricidal cells contributing to increased efficacy of new CD38 CAR-NK cells to target leukemic blasts. BCL2 knockout has synergistic effects with FLT3 inhibitors. Exportin 1 knockout is synergistic with midostaurin treatment in acute myeloid leukemia with FLT3-ITD mutation. Using the results of CRISPR/Cas9 libraries and technology application will allow us to get closer to achieving the goal of curing acute myeloid leukemia in the coming decades.